Application Of Cognitive Behavioral Therapy (CBT) In An Effort To Prevent Postpartum Depression - Illustri , Illustri (Jurnal EduHealth, 2024)
In some countries, the prevalence of postpartum depression is relatively higher. Postpartum depression can have a negative impact on the mother's physical and mental health, and can affect the relationship between mother and baby. Cognitive behavioral therapy (CBT) is an approach that focuses on changing behavior and ways of thinking, as well as increasing the mother's ability to deal with stress and pressure. Therefore, to study this problem, researchers are interested in conducting research on the application of cognitive behavioral therapy (CBT) in an effort to prevent postpartum depression in the working area of the Makrayu health center in Palembang city. The design of this study was quasi experiment, the sample was normal postpartum mothers day 10-40. The number of samples was 15 experimental groups and 15 control groups with purposive consequtive sampling technique. To measure postpartum depression using EPDS (Edinburg Postnatal Depression Scale). From the results of the study it can be concluded that the results of the unpaired t-test obtained a significance value of 0.003, this means "there is a significant mean difference in postpartum depression scores between the intervention group and the control group". Thus it can be concluded that there is an effect of CBT application on postpartum depression. The results of the linear regression test obtained the linearity equation is the application of CBT = 3.863 + 0.208 KF. This means that the application of CBT to postpartum women can reduce depression scores by 3.863 compared to postpartum care without providing CBT-based counseling. Suggestions for each health service are expected to conduct early detection or screening of the possibility of postpartum depression. The screening process should be part of a regular assessment of postpartum women, and anticipate the possibility of postpartum depression.